2016
DOI: 10.1186/s11671-016-1348-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silica Nanoparticles on Antioxidant Potential of Bacillus subtilis IMV B-7023

Abstract: It was found that if introduced into a nutrient medium of 0.05–1 g/L nano-SiO2, the oxidant activity (OA) of the culture medium (CM) of bacilli increased by 43.2–60.1 % and the antioxidant activity (AA) decreased by 4.5–11.8 %. SiO2 nanoparticles had different effects on antiradical activity (ARA) of the CM of Bacillus subtilis IMV B-7023. In particular, nano-SiO2 had no significant effect on the ability of the CM of bacilli to inactivate the 2.2-diphenyl-1-picrylhydrazyl (DPPH·) free radical. However, for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The variation in the peak intensities demonstrates that at the same concentration of zinc oxide, more hydroxyl radicals were produced from the ZnO@SN nanoparticles than from the ZnO nanoparticles. Skoro- chod and coworkers suggested that nano-SiO 2 can mediate the accumulation of hydroxyl radicals on the surface of silica nanoparticles [39]. We hypothesize that the special structure of the silica nanorattles could accumulate more hydroxyl radicals and improve the average efficiency of the hydroxyl radicals produced by ZnO nanoparticles under UV irradiation for a higher detection rate.…”
Section: H+zno+oh à !Oh å ð1þmentioning
confidence: 81%
“…The variation in the peak intensities demonstrates that at the same concentration of zinc oxide, more hydroxyl radicals were produced from the ZnO@SN nanoparticles than from the ZnO nanoparticles. Skoro- chod and coworkers suggested that nano-SiO 2 can mediate the accumulation of hydroxyl radicals on the surface of silica nanoparticles [39]. We hypothesize that the special structure of the silica nanorattles could accumulate more hydroxyl radicals and improve the average efficiency of the hydroxyl radicals produced by ZnO nanoparticles under UV irradiation for a higher detection rate.…”
Section: H+zno+oh à !Oh å ð1þmentioning
confidence: 81%
“…248 Progressively, the Bacillus subtilis RW-I-based lipopeptide biosurfactant was reported as an alternative antioxidant molecule, which could accomplish a better antioxidant capacity in future study. 249 Skorochod et al 250 reported one of the most important applications using nano-SiO 2 , where the 4.5–11.8% of antioxidant potential was diminished through nano-SiO 2 of Bacillus subtilis IMV B-7023. On the other hand, the green nanoparticles showed a significant equilibrium amongst antioxidative protection of cells and boost the antioxidant potential through oxidative stress.…”
Section: Current Applications In Biomedical and Environmental Nanotec...mentioning
confidence: 99%
“…Due to the widespread use of nanoparticles in formulations in recent years, their release into the environment and wastewater is unavoidable (Huang et al 2017) and brings toxicity to biota and/or wastewater treatment processes. Because of increasing concern about the environmental impacts of the latest materials, studies of the toxicity, hazards, fate, and environmental impact of nanoparticles are beginning (Liu et al 2014;Skorochod et al 2016;Ríos et al 2018b).…”
Section: Introductionmentioning
confidence: 99%